Development of a yogurt drink analogue from taro (Colocasia esculenta) corms. - Agui, Therese Angela A.
A yogurt drink analogue from taro was developed. Out of the three formulations differing in the ratio of taro to water, F1 (1:5.5), F2 (1:4), and F3 (1:2.5) subjected to rank test for prefernce, F2 was the Most Prefereed Formulation (MPF). F2 was used in the production of the yogurt drink analogue from taro (YDAT) which was subjected to characterization (physiochemical, proximate, and microbiological properties). YDAT with pH 3.25 had TA of 0.24% (as citric acid) and TSS of 2.08°Brix. YDAT had a proximate composition of 94.77% moisture, 0.78% ash, 0.02% protein, 0.32% fiber, 0.04% fat, and 3.91% carbohydrates. The Lactobacillus spp. count of YDAT was 7.1 x 10⁵ cfu/g. YDAT had low acceptability level of neither like nor dislike. However, addition of mango flavor to the product improved its acceptability rating to like moderately. Consumer testing of mango-flavored YDAT revealed that 70% of the respondents rated the product like moderately to like very much. This showed that the mango-flavored YDAT has potential for commercialization.